Вивчення історії діловодства та його особливостей як основи розуміння сучасної ділової практики - Рой, Є. О. (ХНУРЕ, 2023)
This work examines the historical development of business administration from ancient times to the present day, as well as the fundamental concepts and principles that make up modem business administration. The role and significance of business administration in contemporary business are described. The importance of document management, customer and partner interaction, as well as compliance with legislation in the context of business administration, is discussed in detail.